Guest Editorial for Recent Advances in Medical, Biomedical, and Healthcare Measurements Special Section - Sabrina Grassini; Marco Parvis (IEEE Open Journal of Instrumentation and Measurement)
Measurement is fundamental to medical research and clinical practice. Physicians, clinicians, and medical laboratory scientists must not only be able to detect and diagnose health issues but also have confidence in the results reported by their instruments and measurement methods in order to make the correct decision for their patients. Reliability, accuracy, and efficiency of the implemented methods and devices are, therefore, the main concerns of researchers working in the field of medical measurements and applications.